Nursing assistance in the prevention of surgical site infection - Souza, Viviany Cristieli de (2022)
The present study aims to clarify about surgical site infections - SSI, given the causes of their appearance, as well as their high incidence in the country, being, currently, the third infection that most occurs in hospitalized patients. Thus, it will discuss the role of nursing care in its prevention, as well as the materials and necessary care that must be taken by the team in order to avoid it. This is a literature review by the quantitative method, since it is not intended to exhaust the topic, which was based on materials available on the world wide web. With the research carried out, it was possible to verify that there is a range of preventive measures for SSI, which must be observed according to the surgical procedure performed, always reinforcing the importance of nursing care to avoid infection, given the multiprofessional role. developed. There is a latent need for further research in the field in order to establish new and effective protocols that provide for the role of nurses directly in preventing SSI.